Cubeb (Piper cubeba L.f.): A comprehensive review of its botany, phytochemistry, traditional uses, and pharmacological properties - Drissi, Badreddine; Mahdi, Ismail; Yassir, Mouna; Ben Bakrim, Widad; Bouissane, Latifa; Sobeh, Mansour (Frontiers in Nutrition, 2022)
Piper cubeba L.f. (Piperaceae), known as cubeb, is a popular traditional herbal medicine used for the treatment of many diseases, especially digestive and respiratory disorders. The plant is rich in essential oil, found mainly in fruits, making it economically important. Many traditional utilizations have been also validated from the plant and its isolated compounds. These include antioxidant, antibacterial, anti-inflammatory and, anticancer effects. These biological activities are attributed to the phytochemicals (phenolic compounds, lignans an,d alkaloids) and the essential oil of the plant. The present work aims to provide an up-to-date review on the traditional uses, phytochemistry and pharmacology of the plant and discusses the future perspectives to promote its valorization for nutritional and hehealth-promoting effects.